2020
DOI: 10.1039/d0ra04571c
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-inspired and scalable approach for the synthesis of PdO–2Mn2O3: a nano-material for application in water splitting electro-catalysis

Abstract: A modified co-precipitation method has been used for the synthesis of PdO–2Mn2O3 nanocomposite as an efficient electrode material for the electro-catalytic oxygen evolution (OER) and hydrogen evolution reaction (HER).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 94 publications
(91 reference statements)
2
20
0
Order By: Relevance
“…Although the electrochemical potential of the synthesized material is excellent comparative to the discussed chemically synthesized material, but still this potential could be improved further by varying the parameters, for example, molar concentration of each precursor with the extract, temperature variation, and also by varying the electrolyte or electrolyte concentration. As in one of our previous work 53 in which bio‐fabricated PdO‐2Mn 2 O 3 /Ni‐foam has been used as electrode material, the obtained overpotential value was 359 mV@10 mA/cm 2 . In another study by Zahra et al 52 prepared an efficient hybrid ZnO/Mn 3 O 4 OER nanocatalyst by biomimetic approach with an overpotential value of 420 mV which is closer to the currently synthesized ternary composite at 10 mA/cm 2 current density.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Although the electrochemical potential of the synthesized material is excellent comparative to the discussed chemically synthesized material, but still this potential could be improved further by varying the parameters, for example, molar concentration of each precursor with the extract, temperature variation, and also by varying the electrolyte or electrolyte concentration. As in one of our previous work 53 in which bio‐fabricated PdO‐2Mn 2 O 3 /Ni‐foam has been used as electrode material, the obtained overpotential value was 359 mV@10 mA/cm 2 . In another study by Zahra et al 52 prepared an efficient hybrid ZnO/Mn 3 O 4 OER nanocatalyst by biomimetic approach with an overpotential value of 420 mV which is closer to the currently synthesized ternary composite at 10 mA/cm 2 current density.…”
Section: Resultssupporting
confidence: 54%
“…Using Tauc's plot the optical band gap of bio‐fabricated Mn 2 O 3 /PdO/ZnO was calculated as represented in Equation () below: italicαhvn=()italichvitalicEg. From the above equation the calculated optical band energy for Mn 2 O 3 /PdO/ZnO Nps is 2.2 eV which is ideal for water splitting application as 1.23 eV energy is required to accelerate the reaction 65 and the narrowing of the band energy could enhance the light absorption properties of the material. In one of our previous work, 53 in which phytocapped PdO‐2Mn 2 O 3 exhibited a band gap value of 3.18 eV. In the current investigation with the addition of ZnO (Mn 2 O 3 /PdO/ZnO) the band gap energy is reduced to 2.2 eV with the difference of 0.98 eV.…”
Section: Resultssupporting
confidence: 43%
See 2 more Smart Citations
“…Such correlations and dependencies were observed not only for the IrO x NPs, but also for other electrocatalytic NPs. [32,33] For example, Zahra et al [32] showed that the presence of organic phyto-compounds or carbon-containing capping agents used in the synthesis of the PdO-2Mn 2 O 3 improves the catalytic efficiency of this electrocatalyst toward OER.…”
Section: Introductionmentioning
confidence: 99%